1996
DOI: 10.1159/000188809
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ovariectomy on Glomerular Injury in Hypercholesterolemic Female Imai Rats

Abstract: To clarify the pathogenesis of focal and segmental glomerulosclerosis, we investigated the effect of ovariectomy in hypercholesterolemic female Imai rats. At 5 weeks of age, control female (group 1) and control male rats (group 3) were sham-operated, female rats (group 2) were ovariectomized and male rats (group 4) were castrated. Body weight, blood pressure, urinary protein and serum constituents were checked every 2 months from 2 through 12 months of age. All groups were studied morphologically at 6 months o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…This hypercholesterolemic Imai rat, derived from Sprague-Dawley rats, has a markedly elevated rate of urinary protein excretion, especially in males [1, 2, 3, 4]. Because of this higher susceptibility of male Imai rats to focal and segmental glomerulosclerosis, we previously studied the effects of sex hormones on the development of glomerular injury both in male and in female Imai rats [4, 5, 6, 7]. We found that estrogen replacement therapy does not eliminate the aggravating effect of ovariectomy on glomerular injury and rather aggravates it [8].…”
Section: Introductionmentioning
confidence: 99%
“…This hypercholesterolemic Imai rat, derived from Sprague-Dawley rats, has a markedly elevated rate of urinary protein excretion, especially in males [1, 2, 3, 4]. Because of this higher susceptibility of male Imai rats to focal and segmental glomerulosclerosis, we previously studied the effects of sex hormones on the development of glomerular injury both in male and in female Imai rats [4, 5, 6, 7]. We found that estrogen replacement therapy does not eliminate the aggravating effect of ovariectomy on glomerular injury and rather aggravates it [8].…”
Section: Introductionmentioning
confidence: 99%
“…10 Further, the authors of animal studies of castrated and ovariectomized rats have argued that both the absence of estrogens and the presence of androgens are risk factors for glomerular injury. 11,12 Inada et al, 7 investigated the renal effects of E2 with or without orchiectomy and concluded that E2 was more effective than orchiectomy alone in controlling hyperglycemia, increasing the number of b cells, and reducing glomerular injury. The authors proposed that E2 supplementation that modulates the E2/androgen ratio is a promising therapeutic option for diabetic nephropathy.…”
mentioning
confidence: 99%
“…10 Thus, the combination of the introduction of Medicare ESRD payment reform (in January of 2011) and changes in ESA product labeling (in June of 2011) rapidly led to a 29%-52% reduction in the use of ESAs in dialysis patients across different dialysis organizations. 11 However, the new bundled payment model also raised many concerns about the impact of managing trade-offs that could affect facility and/or provider behaviors and lead to unintended adverse consequences, 12 including worse outcomes for patients with ESRD due to the potential for undertreatment in terms of dialysis time, anemia management, and mineral and bone disorders. 4 In fact, the American Society of Nephrology (ASN) called for close monitoring of not only intermediate quality care outcomes such as lab values, but downstream clinical outcomes such as hospitalizations and mortality.…”
mentioning
confidence: 99%
“…Groups 3 and 4 were ovariectomized and received replacement hormone. Estradiol valerate (Est), purchased from Schering AG Pharmaceutical Division, Germany, diluted in sesame oil to concentrations of 0.1 mg (group 3, Ovx-Est 1, n = 10) and 0.2 mg (group 4, Ovx-Est 2, n = 10) per 0.1 ml, was injected subcutaneously every 4 weeks from 6 to 22 weeks of age according to our previous method [6, 7, 8]. Body weight (BW), urinary protein, serum albumin, total cholesterol (Tchol), blood urea nitrogen (BUN) and serum creatinine (Cr) were investigated every 4 weeks from 12 through 24 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
“…Because of this higher susceptibility of male Imai rats to focal and segmental glomerulosclerosis (FSGS), we previously investigated the effect of estrogen administration on progressive renal injury in male Imai rats, and found that estrogen attenuated progressive glomerular injury [5]. Furthermore, we have found the aggravating effect of ovariectomy on the progression of FSGS, and speculated that sex hormones such as estrogen produced in the ovary may play a protective role in the development of FSGS [6]. On the basis of these findings, in the present study we administered estrogen to ovariectomized hypercholesterolemic female Imai rats to clarify whether the aggravating effect of ovariectomy is due to a lack of estrogen.…”
Section: Introductionmentioning
confidence: 99%